Peran Komunikasi Verbal Dalam Penggunaan Media Gambar Untuk Meningkatkan Kemampuan Berbahasa Mandarin Bagi Anak Taman Kanak-kanak - Maisyah Putri (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2019)
The media image serves to attract attention to more easily understood student learning. delivered by teachersThus verbal communication is still the main communication in learning in the media uses only verbal communication the extent to which it is used and how much affect does that have on increased capacity in. mandarinThe study aimed to identify the role of verbal communication in the use of media images to improve the ability to speak mandarin.The methodology was. This is a descriptive qualitative research methodology .The result showed that media uses pictures is one of the means by which to improve their performance is very effective schooling particularly mandrin language lessons .It was in this picture are serves to attract attention to more easily understood student learning mandarin delivered by teachers .